Teleworking antecedents: an exploration into availability bias as an impediment - Marie-E. Godefroid; Vincent Borghoff; Ralf Plattfaut; Björn Niehaves (Information Systems and e-Business Management, 2024)
Abstract Telework technologies have been known since the 1970s, yet their adoption levels remained low until Covid-19-related lockdowns and curfews. The known rational and non-rational technology acceptance theory and biases cannot fully explain this effect. One of the possible answers to fill this gap could be availability bias which has probably also affected the lag in adopting other technologies. To examine this phenomenon, we conducted a qualitative study with 22 interviews with individuals from different organizational backgrounds and telework adoption levels. Following a combination of inductive and deductive coding, we identified three key aspects of availability bias: intention, cognitive visibility, and cognitive transfer. The findings also allowed us to delineate this bias further from other biases, e.g., the status quo bias, and classical technology acceptance models, e.g., UTAUT. Thereby, this study examines a bias so far only very limitedly researched in the information systems and extends technology acceptance and cognitive bias literature. The findings should also enable practitioners to question their way of working and technology use more thoroughly.
Keywords: 330; Technology acceptance; Cognitive bias; Availability bias; Telework technology; Covid-19